Analisis Struktur Sosial Masyarakat Nelayan Desa Pangandaran Kecamatan Pangandaran - Hayat, Nurul; Lazuardi, Fauzan; Pambudi, Gigih Adhi; Apriansyah, Rifky (Lembaga Yasin AlSys, 2022)
This study examines the social structure of the fishing community in Pangandaran Village, Pangandaran District, Pangandaran Regency. This study uses a qualitative descriptive method, with a literature study approach, namely research whose main source comes from the literature as the main source such as books, journals, articles, and other documents related to the research conducted. The results show that there is a stratification or grouping of people in the fishing community in Pangandaran, there are two groups of fishermen in the Pangandaran fishing community, namely Owner Fishermen (Juragan) and Labor Fishermen (ABK/Jonggol), owner fishermen are fishermen who have all the facilities and infrastructure in catching fish while labor fishermen are fishermen who do not have the facilities and infrastructure to catch fish. In addition, there is also a grouping of fishermen based on their field or occupation, such as tourism fishermen and non-tourism fishermen. Based on the results of research that has been carried out by researchers regarding the analysis of the social structure of the Pangandaran fishing community, there is a patron-client pattern that has an impact on the division of coastal community groups.